Platelet Activation by the apoB/E Receptor-binding Domain of LDL - Relou, I. A. M.; Gorter, G.; van Rijn, J. M. H.; Akkerman, N. J.-W. (Thrombosis and Haemostasis, 2002)
Low density lipoprotein (LDL) increases the sensitivity of human platelets for agonists by activating p38MAPK. Antibody 4G3 disturbs apoB100 binding to the classical apoB/E receptor and inhibits LDLinduced p38MAPK activation, whereas an antibody against a distal domain on apoB100 has no effect. Peptide RLTRKRGLKLA mimics the binding domain of apoB100 called the B-site and activates platelet p38MAPK. Activation by B-site peptide is dose-dependent, transient and followed by desensitization, in accordance with receptor-mediated signalling. A scrambled peptide and a partially homologous peptide RKLRKRLLRDA mimicking the apoB/E receptor binding site of apoE in high density lipoprotein (HDL) also activate p38MAPK albeit 40% weaker, but an uncharged peptide lacks p38MAPK activating capacity. LDL and B-site peptide bind to the same binding sites and initiate similar signalling to p38MAPK and cytosolic phospholipase A2. Thus, LDL and to a lesser extent HDL activate platelets via specific domains in the protein moiety that recognize receptors of the LDL receptor family.
Keywords: LDL; platelets; p38MAPK; apoB100; apoE